An Unusual Case of Abdominal Pain. (30th September 2012) - Desai, Bobby; De Portu, Giuliano
Abstract : Renal calyceal rupture is a usual etiology of abdominal pain in the emergency department. We present a case of unexpected renal calyx rupture in a patient with symptomatology of renal colic. A discussion and review are provided.